Cognitive Dysfunction and Brain Volume Abnormalities in New-Onset Idiopathic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
Neuropsychological function and quantitataive volumetric measurement of grey and white matter of cerebrum were determined in 53 children (ages 8-18 years) with recent-onset idiopathic epilepsy and compared to controls in a study at University of Wisconsin, Madison.